2021
DOI: 10.1038/s41467-021-25853-4
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing aspects of human embryogenesis with pluripotent stem cells

Abstract: Understanding human development is of fundamental biological and clinical importance. Despite its significance, mechanisms behind human embryogenesis remain largely unknown. Here, we attempt to model human early embryo development with expanded pluripotent stem cells (EPSCs) in 3-dimensions. We define a protocol that allows us to generate self-organizing cystic structures from human EPSCs that display some hallmarks of human early embryogenesis. These structures mimic polarization and cavitation characteristic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 58 publications
(94 reference statements)
2
106
0
Order By: Relevance
“…Therefore, if a safety decision cannot be reached using this protective approach further targeted investigations or refinements will be needed. These may include the use of higher-tier approaches, such as hiPSC derived embryos combined with single cell omics techniques ( Shahbazi et al, 2019 ; Zheng et al, 2019 ; Xiang et al, 2020 ; Sozen et al, 2021 ), bespoke microphysiological systems (MPS) and conceptual or agent-based or dynamic models ( Kleinstreuer et al, 2013 ; Villeneuve et al, 2014 ; Capone et al, 2018 ; Thomas et al, 2019 ; Richards et al, 2020 ; Kim et al, 2021 ; Wiedenmann et al, 2021 ), to make a more explicit link between the cellular changes observed and an adverse outcome (a quantitative AOP). Such a bespoke approach will require a significant investment that may not be practical for day-to-day decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if a safety decision cannot be reached using this protective approach further targeted investigations or refinements will be needed. These may include the use of higher-tier approaches, such as hiPSC derived embryos combined with single cell omics techniques ( Shahbazi et al, 2019 ; Zheng et al, 2019 ; Xiang et al, 2020 ; Sozen et al, 2021 ), bespoke microphysiological systems (MPS) and conceptual or agent-based or dynamic models ( Kleinstreuer et al, 2013 ; Villeneuve et al, 2014 ; Capone et al, 2018 ; Thomas et al, 2019 ; Richards et al, 2020 ; Kim et al, 2021 ; Wiedenmann et al, 2021 ), to make a more explicit link between the cellular changes observed and an adverse outcome (a quantitative AOP). Such a bespoke approach will require a significant investment that may not be practical for day-to-day decision making.…”
Section: Discussionmentioning
confidence: 99%
“…These structures form by self-organization under the appropriate culture conditions and recapitulate many of the early developmental events (reviewed in Posfai et al 2021 ; Rossant and Tam 2021 )). More recently, human stem cell-based embryo models have also been created (Fan et al 2021 ; Liu et al 2021 ; Sozen et al 2021 ; Yanagida et al 2021 ; Yu et al 2021 ), but the fidelity to which the human models mimic blastocyst development has been challenged (Zhao et al 2021 ).…”
Section: Main Textmentioning
confidence: 99%
“…Previous human PSC-based blastoid models were not able to recapitulate all the features of the developing blastocysts. Specifically, although blastocyst-like structures have been created from human expanded pluripotent stem cells, induced pluripotent stem cells, or naïve pluripotent stem cells cultured in a different condition, they showed significant divergence from natural blastocysts in marker expression, signaling pathways, cell composition, and cell identity (Sozen et al 2021 ), especially in the TE lineage (Zhao et al 2021 ). These limitations put significant constraints on their utility for modeling embryogenesis.…”
Section: Main Textmentioning
confidence: 99%
“…As noted before, human PSCs appear more readily able to contribute to the TE lineage when they are in a naïve or EPSC conditions than mouse PSCs. This might explain why, contrary to murine blastoids, the majority of human blastoids have been formed from a single cell type and higher yields were reported in some of the single cell type approaches (Kagawa et al, 2021;Sozen et al, 2021;Yanagida et al, 2021) compared to the approach of Fan et al that combines induced TE-like cells with EPSCs (Table 2) (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, this gap is closing with the recent accumulation of studies in both species, including the improved understanding of the similarities and differences in pluripotency ( Brons et al, 2007 ; Tesar et al, 2007 ; Weinberger et al, 2016 ), methods to culture blastocysts towards the post-implantation stage in vitro ( Bedzhov et al, 2014 ; Deglincerti et al, 2016 ; Shahbazi et al, 2016 ), advanced single cell omics studies to demarcate cell identities and regulatory networks that underlie EPI, PrE/HYPO and TE specification ( Nakamura et al, 2015 ; Nakamura et al, 2016 ; Meistermann et al, 2021 ), and the in vitro differentiation of TE and its derivatives ( Castel et al, 2020 ; Io et al, 2021 ). Through the use of human extended pluripotent/expanded potential stem cells (EPSCs), induced pluripotent stem cells (iPSCs) and naïve ESCs, several groups have reported their first successes with human blastoid generation ( Fan et al, 2021 ; Kagawa et al, 2021 ; Liu et al, 2021 ; Sozen et al, 2021 ; Yanagida et al, 2021 ; Yu et al, 2021 ). The methods employed have yet some marked differences between the groups, underlining the different angles and controversies surrounding the cellular subtypes and signaling pathways involved in early human development.…”
Section: Introductionmentioning
confidence: 99%